Academic Self-Efficacy Inventory: Using Rasch Analysis to Develop and Evaluate Self-Efficacy Rating Scales - Yuberti, Y.; Susilowati, N. E.; Velina, Y.; Latifah, S. (Jurnal Pendidikan IPA Indonesia, 2024)
As many studies have proven, self-efficacy positively affects learning performance. Therefore, many instruments have been developed to measure self-efficacy. To be used for educational purposes, the instrument must be proven valid and reliable. This study aims to develop and evaluate the Academic Self-Efficacy Inventory (ASEI) that meets the criteria to be applied as a self-efficacy instrument. This research is a two-phase study designed following the recommendations for scale design and development.A total of 505 Indonesian high school students majoring in science were involved as respondents to test the 20-item rating scale. As a result, all questionnaire items met the fit category with an item reliability score of 0.94, and the unidimensionality scale also met the variance value explained by measures and unexplained variance criteria. Thus, ASEI is declared suitable, reliable, and valid for measuring students' self-efficacy on the topic of light and sound waves. This research provides results in the form of a self-efficacy instrument on the topic of light and sound waves and a validity test with a high value, which is useful for readers to have confidence in the quality of the study results.